Antibodies to Thrombomodulin Induce Receptor-Mediated Endocytosis in Human Saphenous Vein Endothelial Cells - Brisson, Christine; Archipoff, Gisèle; Hartmann, Marie-Louise; Hanau, Daniel; Beretz, Alain; Freyssinet, Jean-Marie; Cazenave, Jean-Pierre (Thrombosis and Haemostasis, 1992)
The membrane glycoprotein thrombomodulin (TM) is an essential endothelial cell (EC) cofactor, which forms a 1:1 stoichiometric complex with thrombin. Binding of thrombin to the high affinity TM receptor transforms its procoagulant activity into an anticoagulant potential, by activating protein C. The fate of TM in the presence of thrombin is still unclear: some authors claim that the thrombin-TM complex is internalized in EC, while others find this complex to be stable for at least 2 h at 37° C on the EC surface. In the present study, we investigated the interactions of thrombin and Fab-fragments of anti-TM antibodies, coupled to 5 or 15 nm gold particles with saphenous vein endothelial cells. Our results demonstrate that TM can be observed both on the plasma membrane and in coated structures only in the presence of anti-TM antibodies. Addition of thrombin decreased the extent of this labeling, while in double labeling experiments, where cells were incubated with 5 nm gold coupled thrombin and 15 nm gold coupled Fab fragments of anti-TM antibodies, thrombin was cointernalized only when anti-TM antibodies were present. These results show that thrombin-TM complex is not significantly internalized in EC. The internalization of this complex induced by anti-TM antibodies could play an important role in the thrombotic complications induced by anti-EC autoantibodies.